Nutritional status and body image perception of Porto Alegre workers - Gerber, Kelli Pereira (2018)
Background: Nutritional status and body image perception play an important role in programs of nutritional surveillance. Aim: to assess the relationship between nutritional status and perception of body image among workers of Porto Alegre, southern Brazil. Materials and Methods: In the current cross-sectional survey, 203 postmen were enrolled. Anthropometric variables included were weight, height, and waist and neck circumference. Body image perception was assessed by Figure Rating Scale developed by Stunkard (1983), adapted by Mash and Roche (1996). Results: Postmen were recruited between 2011 and 2013, in city of Porto Alegre. A mean age of 41.0 ± 11.3 years, and 74 (36.4%) individuals were classified as normal weight, 85 (41.9%), as overweight and 44 (21.7%), as obese. Regarding waist circumference, 115 (76.2%) men and 22 (42.3%) women were classified as adequate. In relation of neck circumference, 82.8% of men and 65.8% of women presented values greater than recommended. According perception of body image, just 60 (29.6%) subjects reported current body image consistent with required body image, and 143 (70.4%) subjects were dissatisfied with their current body image. Besides, postmen satisfied with their body image have significantly lower values of body weight, body mass index, and waist and neck circumference when compared to those non-satisfied. Conclusions: The present study showed a high prevalence of overweight and dissatisfied with body image. Association between status nutritional and body image indicated that the postmen had a good perception of their body image.